Tax compliance of financial services firms: a developing economy perspective - Musimenta, Doreen; Naigaga, Sylvia; Bananuka, Juma; Ssemakula Najjuma, Mariam (Journal of Money Laundering Control, 2019)
The purpose of this study is to examine the contribution of tax morale, compliance costs and tax compliance of financial services firms in Uganda. Design/methodology/approach – This study is cross-sectional and correlational and adopts firm-level data collected using a questionnaire survey of 210 financial services firms in Uganda from which usable questionnaires were received from 152 financial services firms. Findings – Tax morale and compliance costs contribute up to 20.6 per cent of the variance in tax compliance of the financial services firms. Tax morale and tax compliance are positively and significantly associated. Results further indicate that compliance costs and tax compliance are positively and significantly associated. National pride and trust in government and its legal systems as dimensions of tax morale independently are significantly associated with tax compliance. Results also indicate that administration costs and specialist costs as dimensions of compliance costs individually are significantly associated with tax compliance. Research limitations/implications – This study results should be generalized with caution, as they are limited to the financial services firms in Uganda. Originality/value – Whereas there has been a number of studies on tax compliance in both developed and developing countries, this is the first study on the African scene to examine the contribution of tax morale and compliance costs on tax compliance of financial services firms in a single suite. It is unbelievable that the financial services firms, especially commercial banks which are highly regulated by the central bank in many developing countries, can afford to report tax payables year after year.
Keywords: Tax compliance; Tax morale; Compliance costs; Financial services firms